1999
DOI: 10.1046/j.0909-8836.1999.eos107409.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of resin composites with silver‐containing materials

Abstract: Resin composites with antibacterial activity may be useful to decrease the frequency of secondary caries around restorations. The purposes of this study were to investigate the antibacterial activity of light-activated resin composites incorporating one of three silver-containing materials and to evaluate their long-term inhibitory effect against Streptococcus mutans The three types of silver-containing materials, Novaron (N), Amenitop (AM), and AIS, were incorporated into TEGDMA-UDMA-based light-activated res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
3
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 10 publications
5
71
3
5
Order By: Relevance
“…The antibacterial effect of Ag has been reported in various therapies, including Agzeolite in tissue conditioners, 27 gargles containing Agzeolite, 28 and resins containing Ag. 29 In this study, the antibacterial effect of Ag was greater in Aa than in Sm (Figure 4). This was related to the different bacterial sensitivity against Ag, and a further study will be needed.…”
Section: Discussionmentioning
confidence: 90%
“…The antibacterial effect of Ag has been reported in various therapies, including Agzeolite in tissue conditioners, 27 gargles containing Agzeolite, 28 and resins containing Ag. 29 In this study, the antibacterial effect of Ag was greater in Aa than in Sm (Figure 4). This was related to the different bacterial sensitivity against Ag, and a further study will be needed.…”
Section: Discussionmentioning
confidence: 90%
“…15,25,26 Hernández-Sierra et al 27 evaluated the sensitivity of Streptococcus mutans to nano particles of silver (25 nm), zinc oxide (125 nm) and gold (80 nm) and indicated the higher antibacterial properties of nano silver than nano zinc oxide and nanogold; they attributed this results to smaller particle size of nanosilver than nano zinc oxide particles. Concerns exist about the adverse effect of nanoparticle additives on the mechanical properties of composite resins; however, previous studies have reported silver compounds added in 10% concentration or greater to dental materials would significantly reduce compressive strength, elastic modulus and tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial activity of dental materials is conventionally evaluated by using agar diffusion tests (Attin et al, 2001) or determining minimum inhibition concentrations (Yoshida et al, 1999), which are based on water solubility and diffusion rates of antimicrobial agents. Therefore, the use of these assays in determining dental and medical materials with antibacterial properties is questionable (Beyth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%